INFORMATION SYSTEM OF LETTER ARCHIVES AT THE OFFICE PADANG LAWAS DISTRICT GOVERNMENTBARUMUN BARU DISTRICT - Ummi Aminah Hasibuan (Information Technology Studies Journal (ITECH), 2024)
Information systems that support the performance of an agency will be carried out properly and canhandle various data processing using information technology. Information systems are made to facilitate themanagement and storage of data so that it can produce precise and accurate information. The Padang LawasRegency government office is a government agency that is engaged in community service, collection andstorage of all kinds of important documents that will be used as archives. All information regarding thearchive of letters is recorded in the file folder, so that data for archive records in previous years is very difficultto find